2018
DOI: 10.1200/po.18.00225
|View full text |Cite
|
Sign up to set email alerts
|

Association of Germline Genetic Test Type and Results With Patient Cancer Worry After Diagnosis of Breast Cancer

Abstract: Background There are concerns that multigene panel testing compared with BRCA1/ 2-only testing after diagnosis of breast cancer may lead to unnecessary patient worry about cancer because of more ambiguous results. Methods Patients with breast cancer diagnosed from 2013 to 2015 and accrued from SEER registries in Georgia and Los Angeles were surveyed (n = 5,080; response rate, 70%), and responses were merged with SEER data and germline genetic testing and results. We examined patient reports of cancer worry b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…These results are consistent with the COGENT study, a multicenter randomized trial of phone compared to in‐person disclosure of germline genetic test results, which included patients undergoing MGPT, the RESPECT study, a study evaluating the uptake and outcomes of returning MGPT research results to research participants, and a recently published study in breast cancer patients focused on cancer worry exclusively . While we found greater increase in uncertainty among patients undergoing MGPT as compared to targeted testing in the COGENT study, longitudinal data from the COGENT study and these data reveal declines in uncertainty over time .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These results are consistent with the COGENT study, a multicenter randomized trial of phone compared to in‐person disclosure of germline genetic test results, which included patients undergoing MGPT, the RESPECT study, a study evaluating the uptake and outcomes of returning MGPT research results to research participants, and a recently published study in breast cancer patients focused on cancer worry exclusively . While we found greater increase in uncertainty among patients undergoing MGPT as compared to targeted testing in the COGENT study, longitudinal data from the COGENT study and these data reveal declines in uncertainty over time .…”
Section: Discussionsupporting
confidence: 86%
“…In this study, patients with a VUS result had increases in cancer‐specific distress and depression at 6 and 12 months, despite corresponding declines in uncertainty. This is in contrast to the COGENT study where there were no significant differences in this outcome among those with a VUS, and Katz et al who found no impact of test result on cancer worry after MGPT in breast cancer patients . Given conflicting data and different measures and populations across the studies to date, continued evaluation of outcomes by test result, including both those with a positive and VUS result, and in representative clinical populations remains important.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This is consistent with our prior work showing no increase in cancer-related worry associated with testing more genes. 27 Our study is one of the first to demonstrate that moderate-risk PV carriers experience results similarly to those with a high-risk PV without higher levels of uncertainty. The high-and moderate-risk PV groups did not differ significantly in total or subset MICRA scores; this is contrary to our stated hypothesis that moderate-risk carriers would have higher uncertainty than high-risk carriers.…”
Section: Discussionmentioning
confidence: 59%